Inhibition of miR-224 Repressed Cell Growth, Migration and Invasiveness in Gastric Cancer - Shao, Changming; Shao, Qinshu; Shao, Qinshu (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim/Background: MiR-224 has been reported to be associated with many cancers, however, the role of miR-224 in gastric cancer was unclear. Materials and Methods: In the present study, we first used RT-PCR to detect miR-224 level in gastric cancer fresh tissue. Then we performed miR-224 inhibitor transfection in gastric cancer cells, and MTT, cell invasion and migration and colony formation were performed to explore the role of miR-224 in gastric cancer in vitro. Results: The results showed that the relative level of miR-224 in human gastric cancer tissue was significantly higher than that in the adjacent non-tumor gastric mucosa. After transfected by miR-224 inhibitor, the gastric cancer cell proliferation rate was lower compared with the control group, and the migration and invasion are also inhibited by miR-224 inhibitors. The colony number of gastric cancer cells transfected with miR-224 inhibitors was significantly lower than that of the control group. Conclusion: Our results demonstrated that miR-224 is upregulated in gastric cancer. miR-224 inhibitors repressed the proliferation, migration, invasion and colony formation capacity of gastric cancer cells, which indicated that inhibition of miR-224 might be a promising therapeutic option for human gastric cancer.
Keywords: miR-224; Growth; Migration; Invasiveness; Gastric Cancer